Engineering a Mastoparan Peptide Concatemer Prodrug From CircRNA for Cancer Therapy - Grewcock, Declan (2023)
CircRNAs are covalently closed loops of RNA formed as products of RNA backsplicing in mammalian cells. Engineered circRNAs containing a desired coding sequence have been produced using self-splicing introns. Translatable circRNAs require an internal ribosomal entry site or m6A methylation site for translation initiation. CircRNAs with a nucleotide length a multiple of three, a start codon, and no stop codon in the same frame have an infinite open reading frame. This project aimed to produce a mastoparan peptide concatemer prodrug from circRNA for treatment in cancer therapeutics. Anabaena group I self-splicing introns were used to circularise a mastoparan prodrug containing a metalloproteinase cleavage site for activation (construct named Anabaena Mastoparan). RNA circularisation was achieved in vitro but not in mammalian cells, indicating that group I Anabaena introns do not have the catalytic ability to splice in mammalian cells. Mastoparan peptides were detected in vitro and in vivo after adding a Flag tag to the Anabaena Mastoparan construct. However, only peptides produced from unspliced RNA translation were detected. Mastoparan peptides extracted from Anabaena Mastoparan transfected cells caused cytotoxicity when added to the culture medium of MDA-MB-231 and MCF-7 cells. Anabaena Mastoparan transfection did not directly lead to cytotoxicity, demonstrating the effectiveness of mastoparan as a prodrug, only being activated by metalloproteinase cleavage in the extracellular environment.